Reassessing Student Representation: Legal and Managerial Implications of the Absence of a Student Executive Board under Law No. 12 of 2012 - Muhammad Abdul Zalil; Ade Aspandi; Aini Mazaya El Banna; Aip Syarifudin (MASI Mandiri Edukasi, 2026)
This study explores the legal and managerial implications of the absence of a Student Executive Board (Badan Eksekutif Mahasiswa/BEM) at Universitas Pamulang. Law No. 12 of 2012 on Higher Education recognizes students’ rights to form intra-campus organizations as part of their academic and civic development. Nevertheless, Universitas Pamulang operates only through faculty-based associations (HIMA), without a university-level BEM. Using a normative juridical approach and descriptive qualitative analysis, this research reveals that the absence of BEM restricts student representation, weakens interfaculty coordination, and limits participatory decision-making. From a legal perspective, this condition indicates partial non-compliance with statutory obligations regarding organizational rights. From a managerial perspective, it reflects a governance gap that undermines accountability and inclusivity. The findings highlight the need for universities to align legal compliance with participatory management practices to enhance institutional legitimacy and educational quality. The study recommends that higher education institutions establish representative student bodies to foster democratic engagement and fulfill the mandates of national law.